1988
DOI: 10.2307/1541959
|View full text |Cite
|
Sign up to set email alerts
|

Post-Embryonic Development of the Horseshoe Crab

Abstract: Individuals of Limulus polyphemus and Tachypleus tridentatus reached, respectively, the fourteenth-instar and tenth-instar stages during our nine-year rearing experiment. Body sizes were measured using exuviae and body specimens. The results made their growth steps clear, and body sizes of the juveniles at further growth stages could be estimated. We conclude from these data that L. polyphemus males generally molt 16 times to reach maturity in the ninth year; females molt 17 times to reach maturity in the tent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 6 publications
2
38
0
2
Order By: Relevance
“…Therefore, with the exception of the telson, the shape of horseshoe crab at different developmental stages is similar. This is consistent with the results obtained by Sekiguchi et al (1988) on T. tridentatus and Limulus polyphemus. An increase in the wet weight with the prosomal width was isometric (b ≈ 3) in the present study.…”
Section: Growthsupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, with the exception of the telson, the shape of horseshoe crab at different developmental stages is similar. This is consistent with the results obtained by Sekiguchi et al (1988) on T. tridentatus and Limulus polyphemus. An increase in the wet weight with the prosomal width was isometric (b ≈ 3) in the present study.…”
Section: Growthsupporting
confidence: 93%
“…The present study showed that the growth of Tachypleus tridentatus could proceed throughout the year, provided that the seawater temperature was optimal (28 to 30°C). A much slower growth for T. tridentatus, however, was obtained by Sekiguchi et al (1988). In the first year of rearing, the juvenile T. tridentatus remained as 1st instars when reared at room temperature but developed into 2nd instars when reared at 30°C.…”
Section: Growthmentioning
confidence: 93%
See 2 more Smart Citations
“…Dugaan ini sejalan dengan temuan Ehlinger and Tankersley (2004), bahwa salinitas yang tinggi dapat memperlambat pertumbuhan belangkas. Demikian pula hasil penelitian Sekiguchi et al (1988), bahwa pertumbuhan belangkas menurun secara signifikan dengan meningkatnya salinitas.…”
Section: Pembahasanunclassified